1979
DOI: 10.1507/endocrj1954.26.147
|View full text |Cite
|
Sign up to set email alerts
|

Effect of calcium administration on renal responsiveness to parathyroid hormone in pseudohypoparathyroidism type I and II - In comparion with normals, idiopathic and surgical hypoparathyroidism.

Abstract: SynopsisA31-year-old man and a12-year-old girl were diagnosed as pseudohypoparathyroidism (PHP) Type I because of a failure to respond to the administration of parathyroid hormone (PTH) with increased urinary excretion of phosphate and cyclic adenosine-3', 5'-monophosphate (cAMP). A 22-year-old woman was diagnosed as PHP Type II because there was no increase in the urinary excretion of phosphate despite of a marked increase in urinary cAMP excretion.With the combined calcium-PTH infusion or PTH infusion after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Bando et al furthermore suggested that hypokalemia may have contributed in a BS patient to the development PTH-resistance, as documented by performing an EH test before and after correction of serum potassium levels [ 6 ]. PHP type II has also been reported to be associated with calcium or vitamin D deficiency, but the underlying mechanisms remain unresolved [ 7 , 8 ]. Elevated PGE 2 levels, which are known to cause of hypercalciuria, nephrocalcinosis, and osteopenia in BS type 1, have not yet been implicated in the pathogenesis of PTH resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Bando et al furthermore suggested that hypokalemia may have contributed in a BS patient to the development PTH-resistance, as documented by performing an EH test before and after correction of serum potassium levels [ 6 ]. PHP type II has also been reported to be associated with calcium or vitamin D deficiency, but the underlying mechanisms remain unresolved [ 7 , 8 ]. Elevated PGE 2 levels, which are known to cause of hypercalciuria, nephrocalcinosis, and osteopenia in BS type 1, have not yet been implicated in the pathogenesis of PTH resistance.…”
Section: Discussionmentioning
confidence: 99%